2005
DOI: 10.2166/wst.2005.0216
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Legionella to disinfection in hot water distribution systems

Abstract: The efficiency of various disinfection treatments against Legionella was tested on a hot water distribution system (HWDS) pilot unit. The results demonstrated clearly that most Legionella in the networks were fixed in the biofilm at the surface of the pipe (more than 98% for each loop). Chemical treatments (continuous chlorination, hyperchlorination, hydrogen peroxide and peracetic acid mixing) commonly used for the eradication of Legionella in hot water distribution networks appeared to be inadequate for erad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 12 publications
5
28
0
Order By: Relevance
“…Our findings here are in perfect agreement with our previous results. Different studies have evaluated Legionella treatments in water (37,38,57), and a few have evaluated treatment in biofilm (49). Most of the studies demonstrated a transient effect on Legionella, where the initial levels were quickly recovered (49,62,69).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings here are in perfect agreement with our previous results. Different studies have evaluated Legionella treatments in water (37,38,57), and a few have evaluated treatment in biofilm (49). Most of the studies demonstrated a transient effect on Legionella, where the initial levels were quickly recovered (49,62,69).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of VBNC Legionella cells in environmental samples is likely to be associated with variations of biotic or abiotic factors affecting the ecosystem in which Legionella agents proliferate (2,15,26,33). A further factor that fosters the survival and dissemination of Legionella in aquatic environments is the biofilm (23,29). Even if it is not clear whether the pipe material (37) or the type of disinfection influences the development of a biofilm, it was demonstrated previously that the presence of a biofilm reduces the efficacy of disinfection treatments (36).…”
Section: Discussionmentioning
confidence: 99%
“…PAA has been used as a cooling water biocide [32,162], as it has a good potential for the removal of Legionella pneumophila [142,[163][164][165]. The continuous doses used for Legionella removal varied considerably (3-1000 mg/L) and re-growth after treatment was reported [142,[163][164][165].…”
Section: Industrial Effluentsmentioning
confidence: 99%